Clarification of the optimum silica nanofiller amount for electrical treeing resistance - Z. Nawawi; M. A. B. Sidik; M. I. Jambak; C. L. G. Pavan Kumar; Aulia Aulia; M. H. Ahmad; A. A. Abd Jamil (Universitas Ahmad Dahlan, 2019)
This paper aims to clarify the optimum amount of fumed silica (SiO2) nanofiller in resisting the initiation and propagation of electrical treeing in silicone rubber (SiR). Unlike other works, SiR/SiO2 nanocomposites containing seven different weight percentages of SiO2 nanofiller were prepared for this purpose. To achieve the objective, the electrical tree characteristics of the SiR/SiO2 nanocomposites were investigated by comparing the tree initiation voltage, tree breakdown time, tree propagation length and tree growth rate with its equivalent unfilled SiR. Moreover, the structural and morphological analyses were conducted on the SiR/SiO2 nanocomposite samples. The results showed that the SiR, when added with an appropriate amount of SiO2 nanofiller, could result in an improved electrical tree resistance. It implies that the 5 wt% of silica is the optimum amount to achieve the optimal electrical tree resistance such that above 5 wt%, the tree resistance performance has been abruptly reduced, subjected to the agglomeration issue.